An Australian Newcastle Disease Virus With a Virulent Fusion Protein Cleavage Site Produces Minimal Pathogenicity in Chickens. (July 2017) - Bergfeld, Jemma; Meers, Joanne; Bingham, John; Harper, Jennifer; Payne, Jean; Lowther, Sue; Marsh, Glenn; Tachedjian, Mary; Middleton, Deborah
Newcastle disease is an important disease of poultry caused by virulent strains of Newcastle disease virus (NDV). During the 1998 to 2002 outbreaks of Newcastle disease in Australia, it was observed that the mild clinical signs seen in some chickens infected with NDV did not correlate with the viruses' virulent fusion protein cleavage site motifs or standard pathogenicity indices. The pathogenicity of 2 Australian NDV isolates was evaluated in experimentally challenged chickens based on clinical evaluation, histopathology, immunohistochemistry, and molecular techniques. One of these virus isolates, Meredith/02, was shown to induce only very mild clinical signs with no mortalities in an experimental setting, in contrast to the velogenic Herts 33/56 and Texas GB isolates. This minimal pathogenicity was associated with decreased virus replication and antigen distribution in tissues. This demonstrates that the Australian Meredith/02 NDV, despite possessing a virulent fusion protein cleavage site, did not display a velogenic phenotype.